Analysis and Characterization of Quasi-Prepolymers Obtained from Polyethylene Glycol 1500 and 4, 4´-Diphenylmethane-DiIsocyanate. Issue 2 (2015) - Valdés, Bárbara Susana Gregorí; Bordado, Joao Moura; Ribierio, H; Bello, A; Fernández, M; Fernandes, S; Norma, Norma
No abstract available